Production and Physico-Chemical Evaluation of Non-Dairy Probiotic Beverages - Arshad, Armisha; Bacha, Umar; Rao, Momina; Khadim, Mumiza; Ameen, Safia; Hassan, Syeda Rameesha; Dar, Saba Nadeem; Tanweer, Afifa (Nurture, 2022)
Background: Probiotics are live and beneficial bacteria for gut health. The purpose of this study was to develop non-dairy probiotic-rich beverages. Methodology: a fixed quantity of brown sugar was dissolved in distilled water and autoclaved and brown rice was added. All samples were incubated for three days (36 hours) at 37 0C. After every 12 hours, the absorbance of each sample and pH were noted. Likewise, after 36 hours of incubation, all samples were filtered to separate the brown rice. Then filtered beverages were divided into three bottles and two different synthetic flavors and honey were added to one beverage type and stored at -4 0C. All beverages were evaluated for their sensory characteristics, pH, and titratable acidity (storage days). Results: Slight changes in physical and sensory properties of probiotic beverages with synthetic flavor i.e. orange and strawberry were observed while significant changes were seen in the probiotic drink with honey. Probiotic growth continued even after refrigeration after 3rd day of storage which resulted in decreased pH over time. Overall acceptability of all beverages was satisfactory on day 3. Conclusion: The production of nondairy beverages was a successful venture. The drinks had fairly acceptable storage quality. Contribution to literature: Very few studies had examined probiotics of plant origin in the past, particularly, rice. So, this study was designed to fill this gap and to evaluate the potential of rice-based probiotics. Our study revealed that non-dairy probiotic beverages can be produced with grain-based probiotics such as rice.